The Impact of Cognitive Aspects on the Use Organic Fertilizer in Jurit Baru Village - Iskandar, Muhammad Joni (Journal of Agribusiness Science and Rural Development, 2025)
Fertilization aims to replace lost nutrients and increase the supply of nutrients needed by plants to increase plant production and quality. The availability of complete and balanced nutrients that can be absorbed by plants is a determining factor in plant growth and production. One fertilizer with a high nutrient content that is good for plants is organic fertilizer. The aim of this research is to determine farmers' responses based on cognitive aspects to the application of organic fertilizer. The research location was determined purposefully in Jurit Baru Village, East Lombok. The research sample was determined by simple random sampling of as many as 24 lowland rice farmers who were members of 12 farmer groups. The data analysis method uses a Likert scale with an answer score of 1 to 3 for all measurement indicators expressed as a percentage. The research results show that the application of organic fertilizer is based on the cognitive aspects of farmers; most of them know the purpose, benefits, and advantages of organic fertilizer. Meanwhile, the weaknesses are not well known by rice farmers. Overall, farmers have used organic fertilizer in rice farming. However, the dosage used is still a combination of conventional and organic.